2018
DOI: 10.1111/gbi.12284
|View full text |Cite
|
Sign up to set email alerts
|

The taphonomic fate of isorenieratene in Lower Jurassic shales—controlled by iron?

Abstract: Fossil derivatives of isorenieratene, an accessory pigment in brown-colored green sulfur bacteria, are often used as tracers for photic zone anoxia through Earth's history, but their diagenetic behavior is still incompletely understood. Here, we assess the preservation of isorenieratene derivatives in organic-rich shales (1.5-8.4 wt.% TOC) from two Lower Jurassic anoxic systems (Bächental oil shale, Tyrol, Austria; Posidonia Shale, Baden-Württemberg, Germany). Bitumens and kerogens were investigated using cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…S11) produced substantially greater ratios implying a higher Rc of 0.89 %. A similar differential was reported by Reinhardt et al (2018) between kerogen hydropyrolysates and maltene fractions. A slight opposite trend was observed for the ratios of DBT/MDBT (Fig.…”
Section: Aromatic Compoundssupporting
confidence: 86%
See 1 more Smart Citation
“…S11) produced substantially greater ratios implying a higher Rc of 0.89 %. A similar differential was reported by Reinhardt et al (2018) between kerogen hydropyrolysates and maltene fractions. A slight opposite trend was observed for the ratios of DBT/MDBT (Fig.…”
Section: Aromatic Compoundssupporting
confidence: 86%
“…isorenieratane and other aryl isoprenoids -were observed in GC×GC-TOFMS chromatograms of the aromatic fraction of the asphaltite maltenes but isorenieratane was not observed in the hydropyrolysates. Reinhardt et al (2018) observed that, in their study of Lower Jurassic shales, although isorenieratane was present in all the bitumens analysed, it was not present in the corresponding kerogen hydropyrolysates.…”
Section: Quantification Of Carotenoid Products By Gc-mrm Msmentioning
confidence: 86%
“…Samples were analyzed for sedimentary hydrocarbons using an established methodology (Duda et al 2014a(Duda et al , b, 2016(Duda et al , 2020Reinhardt et al 2018). All laboratory materials used were heated to 500 °C for 3 h and/or extensively rinsed with acetone.…”
Section: Analysis Of Sedimentary Hydrocarbons In Bitumen and Kerogen Fractionsmentioning
confidence: 99%
“…9.08 1.60 1.32 5.20-25. 30 Reinhardt et al [57] Chlorobenzene 5.50 1.60 1.11 0.05 Bogacki and Zawadzki [58] Diethyl ether 4.40 1.20 0.71 6.90 Douglas et al [50] Dibutyl ether 3.10 1.20 0.77 0.30 Samec et al [59] Dimethyl ether 3.10 1.30 0.78 Miscible Dong et al [60] Ethyl acetate 6.40 1.80 0.90 7. 94 Li et al [61] Methyl isobutyl ketone [62] F I G U R E 3 Schematic diagram of nanoparticles fracturing chemicals penetration within shale nanopores and cavities However, the particles can be deformed and enter deep into the nanopores within the shale formation.…”
Section: Extraction With Scfsmentioning
confidence: 99%
“…Hexane 1.98 0 0.66 0.01 DiStefano et al [49] Benzene 2.28 0 0.88 0.08 Douglas et al [50] Acetone 21.10 2.91 0.7845 Miscible Wang et al [51] Cyclohexane 2.02 0 0.78 0.005 Ngnie et al [52] Toluene 2.33 0.31 0.87 0.05 Abourriche et al [53] m-Xylene 2.40 0.40 0.86 0.01 Olaguer et al [54] Chloroform 4.81 1.04 1.49 0.81 Akondi et al [55] Carbon tetrachloride 2.20 0 1.58 0.08 Zhao et al [56] Methylene chloride (DCM) [57] Chlorobenzene 5.50 1.60 1.11 0.05 Bogacki and Zawadzki [58] Diethyl ether 4.40 1.20 0.71 6.90 Douglas et al [50] Dibutyl ether 3.10 1.20 0.77 0.30 Samec et al [59] Dimethyl ether 3.10 1.30 0.78 Miscible Dong et al [60] Ethyl acetate 6.40 1.80 0.90 7. 94 Li et al [61] Methyl isobutyl ketone 13.10 2.69 0.80 1.70 Samec et al [59] Cyclohexane 18.2 2.8 0.95 2.3 Dong et al [62] F I G U R E 3 Schematic diagram of nanoparticles fracturing chemicals penetration within shale nanopores and cavities However, the particles can be deformed and enter deep into the nanopores within the shale formation.…”
Section: Solubility In Water (%Wt) Referencementioning
confidence: 99%